(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
In the review, the indicator role of bryophytes of Ukraine is elucidated. Bryophytes are among the most sensitive and stable indicators of environmental condition. Most of bog mosses and some of true mosses are trophoindicators for different types of bogs. Bryophytes are indicators of habitat peculiarities, they indicate the quality of the habitats. Some moss species are indicators of substrates with predominance of a particular chemical compound. They respond to anthropogenic influence, which affects the steppe and forest ecosystems and constitute digressive series, which indicate the degree of anthropogenic transformation of coenoses in these ecosystems. Bryophytes are recognized as indicators of urbanization degree, pollution of residential areas, they are test objects for display of air pollution and indicators of heavy metal accumulation in ecosystems.